2011
DOI: 10.1016/s0929-6646(11)60007-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Conscious Sedation During Upper Gastrointestinal Panendoscopic Examination

Abstract: Women need more analgesic agents than men during panendoscopic examination. There was no significant difference between men and women with regard to anesthetic depth and response to noxious stimuli, as revealed by similar SE and RE values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our results for the impact of gender and fellow involvement are consistent with the relatively limited literature regarding conscious sedation for colonoscopy. Previous studies, including one from our institution, have previously shown women require higher doses of sedative medications for both upper and lower endoscopy and are more likely to report abdominal discomfort during colonoscopy 10,[14][15][16] . The study by Czwornog also showed longer procedure time for female patients, which could also explain the need for higher doses of sedative medications.…”
Section: Discussionmentioning
confidence: 93%
“…Our results for the impact of gender and fellow involvement are consistent with the relatively limited literature regarding conscious sedation for colonoscopy. Previous studies, including one from our institution, have previously shown women require higher doses of sedative medications for both upper and lower endoscopy and are more likely to report abdominal discomfort during colonoscopy 10,[14][15][16] . The study by Czwornog also showed longer procedure time for female patients, which could also explain the need for higher doses of sedative medications.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the same dose per body weight will result in a lower initial plasma concentration of lipophilic drugs in females [ 14 ]. It has been previously reported that females recover more quickly from anesthesia and analgesics than males [ 15 ], and Yen et al [ 16 ] noted that females required more sedatives than males to achieve optimal sedation. Some authors, however, have reported that males may be more likely to exhibit agitation during conscious sedation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some data indicate that even when accounting for differences in body weight by gender, women require more sedatives during endoscopy than men to achieve similar comfort levels. 24 Further study of potential differences in sedation needs during colonoscopy between women and men are needed to clarify ideal dosing parameters for both genders, which may improve colonoscopy utilization.…”
Section: Discussionmentioning
confidence: 99%